2018
DOI: 10.1097/bpb.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport activities after subtalar arthroereisis for correction of pediatric flexible flatfoot

Abstract: The aim of this study was to establish whether children treated with subtalar arthroereisis for flexible flatfoot were able to return to sport activities. We reviewed 49 patients with a mean age at the time of surgery of 10.7 years. The type of sport activities, the number of sessions per week, the time dedicated to each session, and the level achieved were assessed preoperatively and at the last follow-up. Overall, 45 patients returned to sports after surgery. Surgery did not alter the duration, frequency, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 26 publications
3
60
1
1
Order By: Relevance
“…Martinelli et al reported 49 pediatric patients treated with insertion of a permanent implant in the sinus tarsi. 24 A total of 91.8% of these patients returned to normal sports activities after surgery. Needleman treated 28 feet of 23 adult patients with subtalar arthrodesis by sinus tarsi implant, and the occurrence of sinus tarsi discomfort was as high as 42% after implantation.…”
Section: Discussionmentioning
confidence: 93%
“…Martinelli et al reported 49 pediatric patients treated with insertion of a permanent implant in the sinus tarsi. 24 A total of 91.8% of these patients returned to normal sports activities after surgery. Needleman treated 28 feet of 23 adult patients with subtalar arthrodesis by sinus tarsi implant, and the occurrence of sinus tarsi discomfort was as high as 42% after implantation.…”
Section: Discussionmentioning
confidence: 93%
“…They found that duration, frequency, and type of sporting activities did not change after a surgical subtalar procedure. 39 Previous studies on patient satisfaction after treatment with a subtalar arthroereisis only reported satisfaction directly postoperatively in an adult population or with other subtalar arthroereises. 14,18,24,40 The present study is one of the few studies that extensively assessed patient satisfaction in children at a mean follow-up period of 47 months after treatment with the Kalix II implant.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that have provided the evidence basis, safety and effectiveness of this minimally invasive joint sparing procedure. There is evidence of radiographic normalization of osseous realignment (86,87), restoration of navicular height/position (88), maintenance of arch height (89,90), restoration of joint congruity (3), rebalancing of subtalar joint forces (91), decreased strain to the plantar fascia (92), posterior tibial nerve (93), and tendon (94), improved function and pain scores (95), improved ankle joint alignment (96), return to sports activity, and improved emotional status (97). Pediatric patients report a high degrees of satisfaction, and their quality of life was improved and not compromised by the procedure (98,99).…”
Section: Conservative Surgical Treatmentmentioning
confidence: 99%